A discrete limit theorem on the complex plane for one class of general Dirichlet series - Renata Macaitienė (Lietuvos Matematikos Rinkinys)
In the paper a discrete limit theorem in the sense of weak convergence on the complex plane for general Dirichlet series with improved condition is presented.